Predictors of Intensive Treatment in Patients With Obsessive-Compulsive Disorder - du Mortier, Johanna A. M.; Remmerswaal, Karin C. P.; Batelaan, Neeltje M.; Visser, Henny A. D.; Twisk, Jos W. R.; van Oppen, Patricia; van Balkom, Anton J. L. M. (Frontiers in Psychiatry, 2021)
Background: Few studies have investigated which patients with obsessive-compulsive disorder (OCD) do not recover through regular cognitive behavior therapy or pharmacotherapy and subsequently end up in intensive treatment like day treatment or inpatient treatment. Knowing the predictors of intensive treatment in these patients is significant because it could prevent intensive treatment. This study has identified predictors of intensive treatment in patients with OCD. Methods: Using six-year longitudinal data of the Netherlands Obsessive Compulsive Disorder Association (NOCDA), potential predictors of intensive treatment were assessed in patients with OCD (n=419). Intensive treatment was assessed using the Treatment Inventory Costs in Patients with Psychiatric Disorders (TIC-P). Examined potential predictors were: sociodemographics, and clinical and psychosocial characteristics. Logistic Generalized Estimating Equations was used to estimate to what extent the various characteristics (at baseline, two- and four-year assessment) predicted intensive treatment in the following two years, averaged over the three assessment periods. Results: Being single, more severe comorbid depression, use of psychotropic medication, and a low quality of life predicted intensive treatment in the following two years. Conclusions: Therapists should be aware that patients with OCD who are single, who have more severe comorbid depression, who use psychotropic medication, and who have a low quality of life or a drop in quality of life are at risk for intensive treatment. Intensive treatment might be prevented by focusing regular treatment not only on OCD symptoms but also on comorbid depression and on quality of life. Intensive treatment might be improved by providing extra support in treatment or by adjusting treatment to impairments due to comorbid depressive symptoms or a low quality of life.